Effect of Pollen Grain Sources on Success of hybrids in ‘Bedana’ Litchi - Lal, Narayan; Gupta, A. K.; Marboh, E. S.; Kumar, Abhay; Nath, Vishal (International Journal of Bio-resource and Stress Management, 2019)
An experiment was conducted in the year 2018 at ICAR-NRC on Litchi to investigate the effect of different pollen grain sources on fruit set and fruit retention in ‘Bedana’ litchi. The enclosed flower panicles of ‘Bedana’ were hand pollinated with male (M2) pollen from ‘Shahi’, ‘China’, ‘Rose Scented’, ‘SwarnaRoopa’ and ‘Bedana’ flowers. The current season’s pollen as well as one year old pollen stored at 4 °C was used for pollination. The numbers of fruit set and fruit retention per panicle were determined throughout the fruit development period starting from pollination to harvest on a weekly basis. Initial fruit set was higher in all cross-pollination with pollen sources ‘Shahi’, ‘China’ ‘Rose Scented’ and ‘Swarna Roopa’ compared to self-pollination with pollen ‘Bedana’. The final fruit retention in ‘Bedana’ was higher with all sources used for cross-pollination whereas there was no fruit retention in self-pollination where “Bedana” was used as source of pollen grains. Results indicated that cross-pollination in ‘Bedana’ litchi is essential for fruit set and fruit retention. The limited number of initial fruit set resulted in high retention of fruits (1.64% and 1.69%) in ‘Bedana’ with current season and one year old pollen of ‘SwarnaRoopa’. It indicated that number of female flower should be restricted in a panicle for further pollination which would ensure good fruit retention at harvest.